1985
DOI: 10.1113/jphysiol.1985.sp015640
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear magnetic resonance study of metabolism in the ferret heart during hypoxia and inhibition of glycolysis.

Abstract: SUMMARY1. 31P nuclear magnetic resonance was used to measure the relative concentrations of phosphorus-containing metabolites in Langendorff-perfused ferret hearts. Intracellular concentrations of inorganic phosphate ([Pi]i), phosphocreatine ([PCr]i), ATP ([ATP]i) and H+ (pHi) were monitored under control conditions and while oxidative phosphorylation and/or glycolysis were prevented. Mechanical performance was assessed by recording the pressure developed in a balloon placed in the left ventricle.2. Oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
210
5
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(240 citation statements)
references
References 30 publications
24
210
5
1
Order By: Relevance
“…the peak level of PAR, Figure 1Ed) was seen as early as after 5-10 min exposure to H 2 O 2 , before caspase 3 activation, which started at 15 min and peaked at 30-40 min (Figure 4c). Since the resting level of the [ATP] i is B4-7 mM in the heart, 43 it may take time (B40 min exposure, Figure 4c) for it to be completely depleted by activated PARP. It should be noted that PARP/PAR activity starts to slowly decrease after 30 min exposure (Figure 1Ed), at the time when caspase 3 activity peaked (B30-40 min exposure, Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…the peak level of PAR, Figure 1Ed) was seen as early as after 5-10 min exposure to H 2 O 2 , before caspase 3 activation, which started at 15 min and peaked at 30-40 min (Figure 4c). Since the resting level of the [ATP] i is B4-7 mM in the heart, 43 it may take time (B40 min exposure, Figure 4c) for it to be completely depleted by activated PARP. It should be noted that PARP/PAR activity starts to slowly decrease after 30 min exposure (Figure 1Ed), at the time when caspase 3 activity peaked (B30-40 min exposure, Figure 4c).…”
Section: Discussionmentioning
confidence: 99%
“…The main objections against a relevant contribution of KATp-channels are: (i) half maximum inhibition of the channel activity is reached at tens to hundreds of/aM ATP [16,17] whereas measured ATP levels in the ischaemic myocardium are in the range of several mM [18][19][20] which would allow only a few channels to open. In turn this would not be sufficient to explain the large K ÷ efflux; (ii) glibenclamide, a specific blocker of KgTa-Channels, blocks the K ÷ efflux in the ischaemic myocardium only during the first steep phase [4].…”
Section: Discussionmentioning
confidence: 99%
“…With altered metabolic states during ischaemia, it has been reported that intracellular ADP may rise to 180 fM from the physiological value of 10-20 /M (Allen, Morris, Orchard & Pirolo, 1985), although alterations in other NDPs have not been well studied yet. Thus, openings of the dephosphorylated KATP channel induced by increased ADP might be involved in the shortening of the cardiac action potential during ischaemia.…”
Section: Specificity Of Nucleotide Diphosphate Effects On the Katp Chmentioning
confidence: 99%